The Experimental Study of Jeondo-san on Antioxidant Effects - Kwan-Ho Choi; Hyeong-Sik Seo (Korean Pharmacopuncture Institute, 2008)
Objectives : This study was carried out to investigate the antioxidant effects of Jeondo-san(JDS). Methods : The antioxidant effects of JDS were measured by the scavenging for 2,2-Diphenyl-1-picrylhydrazyl(DPPH) radical, th e formation of intracellular glutathione(GSH), the inhibition for reactive oxygen species(ROS). Results : 1. All concentrations of JDS showed antioxidant effect by decreasing the DPPH radicals. 2. All concentrations of JDS did not effect on the formation of intracellular GSH in HaCaT cell. 3. All Concentrations of JDS inhibited the production of ROS in the HaCaT cell stimulated with H2O2. Conclusion : The present date suggest that JDS has effects on the stage of inflammation.